2018
DOI: 10.1016/j.joule.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Perovskite Solar Cells Enabled by All-Crosslinked Charge-Transporting Layers

Abstract: We have designed and synthesized a crosslinkable n-type conjugated molecule, c-HATNA. This c-HATNA electron-transporting layer can be used in conjunction with another crosslinkable hole-transporting layer, c-TCTA-BVP (recently reported by our group), to fabricate an all-crosslinked CTL for PVSC. Benefiting from the lowtemperature crosslinking reactions, the derived cells can achieve high PCE of 16.08% and 13.42% on rigid and flexible substrates, respectively. The device with all-crosslinked CTLs showed impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 75 publications
0
87
0
1
Order By: Relevance
“…The low PCE might come from the low electron mobility of c‐HATNA (6.92 × 10 −5 cm 2 V −1 s −1 ). After the addition of 3% Et 3 N, the mobility was enhanced to 1.14 × 10 −3 cm 2 V −1 s −1 , leading to the enhancement in PCE (18.2%) …”
Section: Nonfullerene Acceptors As Etls In Inverted Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low PCE might come from the low electron mobility of c‐HATNA (6.92 × 10 −5 cm 2 V −1 s −1 ). After the addition of 3% Et 3 N, the mobility was enhanced to 1.14 × 10 −3 cm 2 V −1 s −1 , leading to the enhancement in PCE (18.2%) …”
Section: Nonfullerene Acceptors As Etls In Inverted Pscsmentioning
confidence: 99%
“…a) Structure of c‐HATNA, b) contact angle of PCBM and HATNA, and c) photograph of PCBM‐based device (left) and c‐HATNA‐based device (right) after exposure to water. Reproduced with permission . Copyright 2018, Elsevier.…”
Section: Nonfullerene Acceptors As Etls In Inverted Pscsmentioning
confidence: 99%
“…[12][13][14] The incorporation of additive has been recognized as an efficient methodology to increase the performance of PSCs. [15][16][17][18] Previous reports have demonstrated that incorporating diiodooctane (DIO), NH 4 Cl 19,20 and alkylammonium iodides 11,21 can increase the performance of PSC devices. Furthermore, the inserting of bulky cations can induce formation of 2D perovskites, which has been shown to improve the stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Meanwhile, these trap states create conditions for the infiltration of moisture and oxygen into perovskite layer and subsequently seriously decrease the device stability. Additive engineering [26][27][28][29][30][31][32][33][34] and interface engineering [35][36][37][38][39][40][41] have been regarded as effective strategies to reduce the defect density in PSCs, such as incorporating Phenyl-C61-butyric acid methyl ester (PCBM) [29] into perovskite layer to effectively passivate the defects and minimize the photocurrent hysteresis, inserting self-assembled monolayer of organic molecules with functional groups [36,37] into perovskite/ETL interface to suppress defects Defects, inevitably produced within bulk and at perovskite-transport layer interfaces (PTLIs), are detrimental to power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). [23][24][25] Therefore, it is imperative to seek an effective way to reduce the defects, especially at the PTLIs, for achieving the high-performance PSCs.…”
mentioning
confidence: 99%